(untitled) (Research Announcements "Heritage BG", 2025)
Along with the archaeological, epigraphical and numismatic material, the texts of the ancient, late-antique and early Byzantine authors provide the needed - though fragmentary – information for reconstructing the Thracian history and culture. These texts have been scrutinized and used by the modern historians of Antiquity for several centuries already and it seems that everything has been said. Still, I dare insist that some methodological aspects of their analyses have never been approached and are in fact badly needed. Following a very short summary of the highlights of the Thracian studies so far, the present paper tries to define two methodological principles to be taken into consideration in future research. References: Boteva-Boyanova, Dilya-na. (2021). Antichni, kasnoantični i rannovizantijski izvori za sazdavaneto na rimskata provinciya Trak-iya. In: Peter Delev, Dilyana Boteva-Boyanova, Lily Grozdanova (eds). Jubilaeus VIII: Back to the Sources. Part 1: History and Epigraphy. Sofia, 11-22. Boteva, Dilyana. (2022). Thracia huc usque regnata in prouinciam redigitur. In: Ancient Thrace: Myth and Reality. The Proceedings of the Thirteenth International Congress of Thracology, Kazanlak, September 2017. Volume 2. Sofia, 41-48. Danov, Christo M. (1968). Drevna Trakiya. Sofia. Fol, Alexander. (1972). Politicheska istoriya na trakite: kraya na II hil.pr.n.e. – kraya na V v. pr.n.e.. Sofia: Nauka i izkustvo Fol, Alexander. (1990). Politika i kultura v Drevna Trakiya. Sofia: Nauka i izkustvo. Mitrev, Georgi, Jordan Iliev. (2024). Reineccius i negovata istoriya na drevna Trakiya ot 1595 godina. – Istoriya-History, 32/2, 140-156. Tzvetkova, Julia. (2008). IstoriyanaTrak-ijskiya Hersones (ot Troyanskata vojna do vremeto na rimskoto zavoevanie. Veliko Tarnovo: Faber. Vanova, Lilyana, Galiley Lambev, Panto Kolev, Boyko Kiryakov (compilers). (1986). Balgarskite zemi v knigi, atlasi, karti, gravjuri i risunki ot kolekciyatana dr. Simeon Simov. Sofia. Balot, Ryan K., Sara Forsdyke and Edith Foster (eds.). (2017). The Oxford Handbook of Thucydides. Oxford. Cary, Felix. (1752). Histoire des Rois de Thrace et de ceux du Bosphore Cimmerien eclaircie par les medailles. Paris. Danov, Christo M. (1976). Altthrakien. Walter de Gruyter: Berlin, New York. Euben, J. Peter. (1986). Thucydides by W. Robert Connor. Princeton: Princeton University Press, 1984. Pp. 260. - Political Theory, 14/1, 140-144. Haverkamp, Sigebert. (1737). Algemeene Histori der Zaaken in Asie, Afrika, en Europe, en in Derzelver koningryken, Landschappen, Staaten en Steden Zederd het ophouden der Fabel Eeuwe tot op de Heerschappy van Karel den Grooten. Graavenhaage: by Pieter de Hondt. https://books.google.bg/books/about/Algemeene (accessed 20.08.2024). Heidmann, Christophor. (1658). Europa Sive Manuductio Ad Geographiam Veterem In Illustri Academia Iulia Cum locorum indice olim explicate. Buno. https://books.google.bg/books?id=vPhjAAAAcA AJ&printsec=frontcover&hl=bg#v=onepage&q&f=false (accessed 17.08.2024). Helm, Rudolf (Hrsg). (1956). Eusebius Werke, 7. Band: Die Chronik des Hieronymus. Berlin. Hornius, Georgius. (1666). Arca Noæ sive historia imperiorum et regnorum a condito orbe ad nostra tempora. Leiden: Ex officina Hackiana. https://archive.org/details/bub_gb_vQ__G5XkS7wC/page/122/mode/2up (accessed 20.08.2024). Irwin, Elizabeth. (2023). Labouring for Truth in Thucydides. In: Polly Low (ed.). The Cambridge Companion to Thucydides. Cambridge University Press, 110 – 126. Jackson, John (Transl.). (1970). Tacitus in five volumes. Vol. 4: Annals books IV-VI, XI-XII. Loeb Classical Library, London –Cambridge MA. Karst, Josef (Übstz.). (1911). Die Chronik des Eusebius aus dem Armenischen übersetzt von Dr. Josef Karst. Leipzig. Konaris, Michael D. (2022). Thucydides and the Causes of the Peloponnesian War in nineteenth-century Historiography: The Case of Konstantinos Paparrigopoulos versus George Grote and Ernst Curtius. In: Nanno Marinatos and Robert K. Pitt (eds.). Thucydides the Athenian. (= College Year in Athens Papers 1). Athens, 287-305. Loraux, Nicole. (1980). Thucycide n’est pas un collegue. – Quaderni di Storia, 12, 55-81. Loraux, Nicole. (2011). Thucydides is not a Colleague. In: John Marincola (ed.). Greek and Roman Historiography. Oxford Readings in Classical Studies. Oxford; New York: Oxford University Press, 17-42. Low, Polly A. (ed.). (2023). The Cambridge Companion to Thucydides. Cambridge University Press. Marinatos, Nanno, Robert K. Pitt (eds.). (2022). Thucydides the Athenian. (= College Year in Athens Papers 1). Athens. Marsigli, Luigi Ferdinando. (1681). Osservazioni Intorno al Bosforo Tracio Overo Canale di Constantinopoli Rappresentate in Lettera Alla Sacra Real Maestá Cristina Regina di Svezia. Roma. https://books.google.bg/books?id=tp1XSfoEeFAC&printsec=frontcover&hl=bg#v=onepage&q&f=false (accessed 17.08.2024). Marsili, Luigi Ferdinando. (1726). Danubius Pannonico Mysicus. Observationibus geographicis, astronomicis, hydrographicis, historicis, physicis perlustratus et in sex tomos digestus ab Aloysio Ferd. Com. Marsili. Tomus Secundus: De antiquitatibus Romanorum ad ripas Danubii. The Hague, Amsterdam. Marsili, Luigi Ferdinando. (1734). Description du Danube depuis la Montagne de Kalenberg en Autriche jusqu’au confluent de la rivière Jantra dans la Bulgarie..., traduite du Latin, t. I-VI. A la Haye. Migne, Jacques-Paul (ed.). (1866). Patrologia Latina (= Patrologiae cursus completus: seu biblioteca universalis, integra uniformis, commode, oeconomica, omnium SS. Patrum, doctorum scriptorumque ecclesiasticorum, sive Latinorum, sive Graecorum, qui ab aevo apostolico ad usque Innocentii III tempora... floruerunt), 27. Paris. Müller-Strübung, Herman. (1885). Die Glaubwürdigkeit des Thukydides geprüft an seiner Darstellung der Belagerung von Plataia. - Neue Jahrbücher für Philologie und Paedagogik, 55, Bd. 131, Leipzig, 289-348. Nývlt, Pavel. (2018). Discrepancies in Thucydides. In: Peter Fraňo, Michal Habaj (eds.), Antica Slavica. Trnava, 61-76. Phillips, Philip L. (1914). A List of Geographical Atlases in the Library of Congress. Vol. III. Washington. https://archive.org/details/listofgeographic03libr/page/114/mode/2up (accessed 20.08.2024). Pindikova, Galina (ed.). (2006). The Bulgarian Lands from the Antiquity to the Recent Days in Atlases, Maps, Engravings and Books from the Collection of Dr. Simeon Simov. Sofia: General Department of Archives. Plant, Ian. (2016). The “Life of Thucydides” by Marcellinus. – Ancient History, 46, 117-144. Popper, Karl R. (2002). The Poverty of Historicism. London and New York. Popper, Karl R. (2013). The Open Society and Its Enemies. Princeton University Press. https://books.google.bg/books?id=EaKc0RRqlvYC&pg=PA169&redir_esc=y#v=onepage&q&f=false (accessed 12.12.2024). Reineccius, Reinerus. (1595). Historia Ivlia, Siue Syntagma Heroicvm. 2, Comprehendens Monarchiam Secvndam, quae censetur Regnis Medorum & Persarum: Comprehendens distinctè & singulatim reliqua eiusdem temporis imperia, id est, Regna XVI. Dynastiam vnam, Tyrannides XIX. Respvblicas XIV. Helmaestadii: Kirchnerus. https://www.digitale-sammlungen.de/en/view/bsb10313347?page=138,139 (accessed 29.11.2024). Rengakos, Antonios, Antonis Tsakmakis (eds.). (2006). Brill’s Companion to Thucydides. Leiden–Boston. Schachermeyr, Fritz. (1976). Geleitwort. In: Chr. M. Danov. Altthrakien. Walter de Gruyter: Berlin, New York, pp. V-VI. Schoene, Alfred (ed.). (1866). Evsebi Chronicorvm libri dvo. Vol. II: Evsebi Chronicorvm Canonum. Berolini. Theodossiev, Nikola. (2015). An Introduction to Studying Ancient Thrace. In: Julia Valeva, Emil Nankov, and Denver Graninger (eds.). A Companion to Ancient Thrace. John Wiley & Sons, Inc., 3-11.